A carbon cloth electrode for vanadium battery and preparation method thereof

By preparing carbon cloth electrodes loaded with reduced graphene oxide and manganese cobalt oxide, the problems of poor catalytic activity and low effective reaction area of ​​existing vanadium battery electrode materials are solved, and the voltage efficiency, energy efficiency and capacity maintenance of vanadium battery are improved. rate effect.

CN119029219BActive Publication Date: 2025-02-07HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411463295.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-07
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing vanadium battery electrode materials have poor catalytic activity and low effective reaction area, which limits the performance of vanadium battery operating at high current density.

Method used

By preparing a carbon cloth electrode for vanadium batteries, materials such as graphite powder, sodium nitrate, concentrated sulfuric acid, potassium permanganate, citrate compounds and cobalt sulfate were formed by hydrothermal reduction and calcination, and reducing oxidation was formed by hydrothermal reduction and calcination. Carbon cloth electrodes for graphene and manganese cobalt oxide.

Benefits of technology

It enhances the bonding force between metal oxides and carbon materials, reduces the charge transfer resistance, improves the voltage and energy efficiency of the battery, promotes the transmission of electrons, and improves the capacity retention rate of vanadium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119029219B_ABST
    Figure CN119029219B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of all-vanadium liquid flow battery electrodes, and discloses a carbon cloth electrode for vanadium batteries and a preparation method thereof, comprising the following steps: preparing graphene oxide; reducing graphene oxide while in-situ growing a manganese cobalt oxide precursor on graphene; loading the catalyst precursor on the carbon cloth through an adhesive and calcining at high temperature to prepare a carbon cloth electrode loaded with reduced graphene oxide and manganese cobalt oxide. The present invention combines the manganese source generated when preparing graphene oxide with a cobalt source to achieve in-situ growth of manganese cobalt oxide on the surface of graphene oxide, thereby enhancing the binding force between the metal oxide and the carbon material and reducing the charge transfer resistance; a citrate compound converts potassium permanganate into manganese sulfate, then complexes manganese ions and cobalt ions, and acts as a reducing agent to reduce graphene oxide; the conductivity of graphene oxide is improved, and the ohmic polarization of the battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of all-vanadium liquid flow batteries, and in particular to a carbon cloth electrode for a vanadium battery and a preparation method thereof. Background Art

[0002] All-vanadium liquid flow batteries (vanadium batteries for short) have fixed redox pairs, so the most direct and simple way to reduce costs is to reduce the size of the battery stack by maximizing power density and to achieve effective use of electrolytes by improving electrolyte utilization. Maximizing both power density and electrolyte utilization depends mainly on reducing battery energy losses, including reducing activation polarization, ohmic polarization, and concentration polarization. Therefore, designing electrode structure and surface properties to improve electrochemical reactions and electron / ion transport is crucial to achieving optimal battery performance. Traditional electrode materials such as carbon cloth, graphite felt, and carbon paper have serious kinetic problems. The poor catalytic activity of redox reactions and the low effective reaction area of ​​vanadium ions limit the operation of vanadium batteries at high current densities. Therefore, increasing the specific surface area and catalytic activity of the electrode is the key to improving the performance of vanadium batteries. Summary of the invention

[0003] The object of the present invention is to provide a carbon cloth electrode for vanadium battery and a preparation method thereof, so as to overcome the deficiencies in the prior art.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] The present application discloses a method for preparing a carbon cloth electrode for a vanadium battery, comprising the following steps:

[0006] S1. Add 10-20 parts by mass of graphite powder, 5-10 parts by mass of sodium nitrate and 420-850 parts by mass of concentrated sulfuric acid in an ice water bath, mix well, add 30-60 parts by mass of potassium permanganate, and stir to react; after the reaction, add 500-1000 parts by mass of deionized water, and stir for a second reaction; then add 50-100 parts by mass of a citrate compound to the suspension, mix well, and perform ultrasonic peeling to obtain a mixed solution containing graphene oxide, manganese sulfate and citrate;

[0007] S2, adding 60-120 parts by mass of cobalt sulfate to a mixed solution containing graphene oxide, manganese sulfate and citrate, mixing, and performing a hydrothermal reduction reaction; after the reaction is completed, centrifuging, collecting the remaining solid, and drying to obtain a composite material of reduced graphene oxide and manganese cobalt oxide precursor;

[0008] S3. Disperse and dissolve the composite material of reduced graphene oxide and manganese cobalt oxide precursor and adhesive in deionized water, stir evenly to obtain aqueous slurry; immerse the carbon cloth electrode in the aqueous slurry, take out, dry and calcine to obtain a carbon cloth electrode loaded with reduced graphene oxide and manganese cobalt oxide.

[0009] Preferably, the citrate compound in step S1 is one of citric acid, sodium citrate and ammonium citrate.

[0010] Preferably, the stirring reaction process in step S1 is: first stirring the reaction at a temperature of 15-20° C. for 1-3 hours, and then raising the temperature to 30-40° C. for 30-60 minutes.

[0011] Preferably, the secondary stirring reaction temperature in step S1 is 95-98° C. and the time is 20-30 min.

[0012] Preferably, in step S1, the ultrasonic stripping time is 6 to 10 hours.

[0013] Preferably, in step S2, the temperature of the hydrothermal reduction reaction is 60-100° C., and the reaction time is 4-8 hours.

[0014] Preferably, in step S3, the adhesive is one of polyvinyl alcohol water-based adhesive, polyurethane water-based adhesive, and epoxy resin water-based adhesive.

[0015] Preferably, in step S3, the mass ratio of the composite material of reduced graphene oxide and manganese cobalt oxide precursor, the adhesive and deionized water is (1-2):1:20.

[0016] Preferably, in step S3, the calcination temperature is 380-430° C., and the calcination time is 2-4 hours.

[0017] A carbon cloth electrode for a vanadium battery is prepared by using the above-mentioned method for preparing a carbon cloth electrode for a vanadium battery.

[0018] Beneficial effects of the present invention:

[0019] The present invention combines the manganese source and the cobalt source generated when preparing graphene oxide, realizes the in-situ growth of manganese cobalt oxide on the surface of graphene oxide, enhances the binding force between the metal oxide and the carbon material, reduces the charge transfer resistance, and improves the voltage efficiency and energy efficiency of the battery.

[0020] The present invention uses a citrate compound. After potassium permanganate is converted into manganese sulfate, the remaining citrate can complex manganese ions and cobalt ions, and can also be used as a reducing agent to reduce graphene oxide, thereby improving the conductivity of graphene oxide, reducing the ohmic polarization of the battery, and thus improving the voltage efficiency and energy efficiency of the vanadium battery.

[0021] The adhesive enhances the interaction between the catalyst and the carbon cloth. After calcination, it can effectively prevent the catalyst from falling off during the cycle, and form a cross-linked conductive network on the surface of the carbon cloth, which promotes the transmission of electrons and improves the voltage efficiency, energy efficiency and capacity retention rate of the vanadium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the carbon cloth in Example 1 of the present invention;

[0023] Figure 2 It is a relationship diagram between the redox peak current and the square root of the scan rate in the cyclic voltammetry curves of the carbon cloth in Example 1 of the present invention and Comparative Example 1;

[0024] Figure 3 The Raman curves of the carbon cloth in Example 1 and Comparative Example 2 of the present invention are shown. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0026] A method for preparing a carbon cloth electrode for a vanadium battery comprises the following steps:

[0027] S1. Add 10-20 parts by mass of graphite powder, 5-10 parts by mass of sodium nitrate and 420-850 parts by mass of concentrated sulfuric acid in an ice water bath, mix well, add 30-60 parts by mass of potassium permanganate, stir and react at 15-20° C. for 1-3 hours, then raise the temperature to 30-40° C. and stir and react for 30-60 minutes; after the reaction, add 500-1000 parts by mass of deionized water, stir again at 95-98° C. for 20-30 minutes; then add 50-100 parts by mass of a citrate compound to the suspension, mix well, and perform ultrasonic peeling for 6-10 hours to obtain a mixed solution containing graphene oxide, manganese sulfate and citrate;

[0028] S2, adding 60-120 parts by mass of cobalt sulfate to a mixed solution containing graphene oxide, manganese sulfate and citrate, and mixing, and performing a hydrothermal reduction reaction at 60-100° C. for 4-8 hours; after the reaction is completed, centrifuging, collecting the remaining solid, and drying to obtain a composite material of reduced graphene oxide and manganese cobalt oxide precursor;

[0029] S3. Disperse and dissolve 5 to 10 parts by mass of a composite material of reduced graphene oxide and a manganese cobalt oxide precursor and 5 parts by mass of an adhesive in 100 parts by mass of deionized water, and stir evenly to obtain an aqueous slurry; immerse a carbon cloth electrode in the aqueous slurry, take it out, dry it, and then calcine it at 380 to 430°C for 2 to 4 hours to obtain a carbon cloth electrode loaded with reduced graphene oxide and manganese cobalt oxide.

[0030] Embodiment 1: comprising the following steps

[0031] This embodiment is specifically obtained by the following operations:

[0032] S1. Add 10 parts by mass of graphite powder, 5 parts by mass of sodium nitrate and 420 parts by mass of concentrated sulfuric acid in an ice water bath, mix well, add 30 parts by mass of potassium permanganate, stir and react at 15°C for 1 hour, then raise the temperature to 30°C and stir and react for 30 minutes; after the reaction, add 500 parts by mass of deionized water, stir twice at 95°C for 20 minutes; then add 50 parts by mass of citric acid to the suspension, mix well, and perform ultrasonic peeling for 6 hours to obtain a mixed solution containing graphene oxide, manganese sulfate and citrate;

[0033] S2, adding 60 parts by mass of cobalt sulfate to a mixed solution containing graphene oxide, manganese sulfate and citrate, mixing, and performing a hydrothermal reduction reaction at 60° C. for 4 hours; after the reaction is completed, centrifuging, collecting the remaining solid, and drying to obtain a composite material of reduced graphene oxide and manganese cobalt oxide precursor;

[0034] S3. Disperse and dissolve 5 parts by mass of a composite material of reduced graphene oxide and a manganese cobalt oxide precursor and 5 parts by mass of a polyvinyl alcohol aqueous adhesive in 100 parts by mass of deionized water, and stir evenly to obtain an aqueous slurry; immerse a carbon cloth electrode in the aqueous slurry, take it out, dry it, and then calcine it at 380°C for 2h to obtain a carbon cloth electrode loaded with reduced graphene oxide and manganese cobalt oxide.

[0035] Embodiment 2: comprising the following steps

[0036] S1. Add 15 parts by mass of graphite powder, 7.5 parts by mass of sodium nitrate and 630 parts by mass of concentrated sulfuric acid in an ice water bath, mix well, add 45 parts by mass of potassium permanganate, stir and react at 18°C ​​for 2h, then raise the temperature to 35°C and stir and react for 45min; after the reaction, add 750 parts by mass of deionized water, stir twice at 96°C for 20-30min; then add 75 parts by mass of sodium citrate to the suspension, mix well, and perform ultrasonic peeling for 8h to obtain a mixed solution containing graphene oxide, manganese sulfate and citrate;

[0037] S2, adding 90 parts by mass of cobalt sulfate to a mixed solution containing graphene oxide, manganese sulfate and citrate, mixing, and performing a hydrothermal reduction reaction at 80° C. for 6 hours; after the reaction is completed, centrifuging, collecting the remaining solid, and drying to obtain a composite material of reduced graphene oxide and manganese cobalt oxide precursor;

[0038] S3. Disperse and dissolve 7.5 parts by mass of a composite material of reduced graphene oxide and a manganese cobalt oxide precursor and 5 parts by mass of a polyurethane aqueous adhesive in 100 parts by mass of deionized water, and stir evenly to obtain an aqueous slurry; immerse a carbon cloth electrode in the aqueous slurry, take it out, dry it, and then calcine it at 405°C for 3 hours to obtain a carbon cloth electrode loaded with reduced graphene oxide and manganese cobalt oxide.

[0039] Embodiment 3: comprising the following steps

[0040] S1. Add 20 parts by mass of graphite powder, 10 parts by mass of sodium nitrate and 850 parts by mass of concentrated sulfuric acid in an ice water bath, mix well, add 60 parts by mass of potassium permanganate, stir and react at 20°C for 3 hours, then raise the temperature to 40°C and stir and react for 60 minutes; after the reaction, add 1000 parts by mass of deionized water, stir twice at 98°C for 30 minutes; then add 100 parts by mass of ammonium citrate to the suspension, mix well, and perform ultrasonic peeling for 10 hours to obtain a mixed solution containing graphene oxide, manganese sulfate and citrate;

[0041] S2, adding 120 parts by mass of cobalt sulfate to a mixed solution containing graphene oxide, manganese sulfate and citrate, and mixing, and performing a hydrothermal reduction reaction at 100° C. for 8 hours; after the reaction is completed, centrifuging, collecting the remaining solid, and drying to obtain a composite material of reduced graphene oxide and manganese cobalt oxide precursor;

[0042] S3. Disperse and dissolve 10 parts by mass of a composite material of reduced graphene oxide and a manganese cobalt oxide precursor and 5 parts by mass of an epoxy resin aqueous adhesive in 100 parts by mass of deionized water, and stir evenly to obtain an aqueous slurry; immerse a carbon cloth electrode in the aqueous slurry, take it out, dry it, and then calcine it at 430°C for 4 hours to obtain a carbon cloth electrode loaded with reduced graphene oxide and manganese cobalt oxide.

[0043] Comparative Example 1:

[0044] This comparative example is a blank control group, that is, an untreated blank carbon cloth is used.

[0045] Comparative Example 2:

[0046] The preparation process of this comparative example is different from that of Example 1 only in that hydrogen peroxide is used instead of citric acid in step S1.

[0047] Comparative Example 3:

[0048] The preparation process of this comparative example is different from that of Example 1 only in that no adhesive is added in step S3.

[0049] Figure 1 This is a scanning electron microscope image of the carbon cloth electrode prepared in Example 1. It can be seen that the surface of the carbon cloth is covered with reduced graphene oxide and manganese cobalt oxide, forming a cross-linked conductive network, which is beneficial to the transmission of electrons. Figure 2 This is the relationship between the redox peak current and the square root of the scan rate in the cyclic voltammetry curves of the carbon cloth in Example 1 and Comparative Example 1. It can be seen that at the same scan rate, the carbon cloth modified by reduced graphene oxide and manganese cobalt oxide has a higher redox peak current, which proves that the electrochemical surface area and electrical conductivity of the carbon cloth in Example 1 are higher, and therefore the carbon cloth prepared in Example 1 has better catalytic activity. Figure 3 is the Raman curve of the carbon cloth in Example 1 and Comparative Example 2. It can be seen that the I D / I G The value is higher, which proves that the oxygen content of graphene in Example 1 is significantly reduced, the degree of reduction of graphene oxide is increased, and the conductivity is improved.

[0050] The carbon cloth electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were assembled into battery stacks and subjected to charge and discharge tests under the same test conditions, and the battery coulombic efficiency, voltage efficiency, energy efficiency, and capacity retention rate after 100 cycles were recorded. The test results are shown in Table 1:

[0051] Table 1. Performance test results of carbon cloth electrodes in examples and comparative examples

[0052]

[0053] As can be seen from Table 1, compared with Comparative Example 1 and Comparative Example 3, Examples 1 to 3 have higher voltage efficiency, energy efficiency and capacity retention rate, mainly because the present invention combines the manganese source generated when preparing graphene oxide with the cobalt source to achieve in-situ growth of manganese cobalt oxide on the surface of graphene oxide, enhances the binding force between the metal oxide and the carbon material, reduces the charge transfer resistance, and improves the voltage efficiency and energy efficiency of the battery; and the adhesive enhances the interaction between the catalyst and the carbon cloth, and after calcination, it can effectively prevent the catalyst from falling off during the cycle, and forms a cross-linked conductive network on the surface of the carbon cloth, which promotes the transmission of electrons and improves the voltage efficiency, energy efficiency and capacity retention rate of the vanadium battery; Compared with Comparative Example 2, Examples 1 to 3 have higher voltage efficiency and energy efficiency, mainly because the present invention uses a citrate compound, and after converting potassium permanganate into manganese sulfate, the remaining citrate can complex manganese ions and cobalt ions, and can also be used as a reducing agent to reduce graphene oxide, thereby improving the conductivity of graphene oxide, reducing the ohmic polarization of the battery, and thus improving the voltage efficiency and energy efficiency of the vanadium battery.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon cloth electrode for a vanadium battery, characterized in that: The following steps are involved: Step S1: adding 10-20 parts by mass of graphite powder, 5-10 parts by mass of sodium nitrate and 420-850 parts by mass of concentrated sulfuric acid to an ice water bath, adding 30-60 parts by mass of potassium permanganate after mixing, stirring for reaction, adding 500-1000 parts by mass of deionized water after the reaction is completed, performing a secondary stirring reaction, adding 50-100 parts by mass of a citrate compound after the reaction is completed, mixing evenly and then performing ultrasonic peeling to obtain a mixed solution containing graphene oxide, manganese sulfate and citrate; Step S2: adding 60 to 120 parts by mass of cobalt sulfate to a mixed solution containing graphene oxide, manganese sulfate and citrate, mixing, and performing a hydrothermal reduction reaction. After the reaction is completed, centrifuging, collecting the remaining solid, and drying to obtain a composite material of reduced graphene oxide and manganese cobalt oxide precursor; Step S3: Add the composite material of reduced graphene oxide and manganese cobalt oxide precursor and adhesive into deionized water, stir evenly to obtain an aqueous slurry; immerse the carbon cloth electrode in the aqueous slurry, take out, dry and calcine to obtain a carbon cloth electrode loaded with reduced graphene oxide and manganese cobalt oxide; the adhesive is one of polyvinyl alcohol aqueous adhesive, polyurethane aqueous adhesive and epoxy resin aqueous adhesive; the calcination temperature is 380~430℃, and the calcination time is 2~4h.

2. The method for preparing a carbon cloth electrode for a vanadium battery according to claim 1, characterized in that: In step S1, the citrate compound is one of citric acid, sodium citrate and ammonium citrate.

3. The method for preparing a carbon cloth electrode for a vanadium battery according to claim 1, characterized in that: The stirring reaction process in step S1 is: first stirring the reaction at 15-20° C. for 1-3 hours, and then raising the temperature to 30-40° C. for 30-60 minutes.

4. The method for preparing a carbon cloth electrode for a vanadium battery according to claim 1, characterized in that: The secondary stirring reaction temperature in step S1 is 95-98° C. and the time is 20-30 min.

5. The method for preparing a carbon cloth electrode for a vanadium battery according to claim 1, characterized in that: The time of ultrasonic stripping in step S1 is 6 to 10 hours.

6. The method for preparing a carbon cloth electrode for a vanadium battery according to claim 1, characterized in that: The temperature of the hydrothermal reduction reaction in step S2 is 60-100° C., and the reaction time is 4-8 hours.

7. The method for preparing a carbon cloth electrode for a vanadium battery according to claim 1, characterized in that: In the step S3, the mass ratio of the composite material of reduced graphene oxide and manganese cobalt oxide precursor, adhesive and deionized water is (1-2):1:

20.

8. A carbon cloth electrode for a vanadium battery, characterized in that: The carbon cloth electrode is prepared by the method for preparing a carbon cloth electrode for a vanadium battery as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Magnesium-cobalt oxide / graphene composite material used as supercapacitor electrode material and preparation method thereof

    CN105938761A

  • Apparatus comprising manganese-cobalt spinel oxide / carbon catalyst

    US20200295380A1